Battery longevity of implantable cardioverter-defibrillators and cardiac resynchronization therapy defibrillators: technical, clinical and economic aspects. An expert review paper from EHRA. Issue 12 (10th May 2018) - Boriani, Giuseppe; Merino, Josè; Wright, David J; Gadler, Fredrik; Schaer, Beat; Landolina, Maurizio
Abstract: In recent years an extension of devices longevity has been obtained for implantable cardioverter-defibrillators (ICDs), including ICDs for cardiac resynchronization therapy (CRT-D) through improved battery chemistry and device technology and this implies important clinical benefits (reduced need for device replacements and associated complications, particularly infections), as well as economic benefits, in line with patient preferences and needs. From a clinical point of view, the availability of this improvement in technology allows to better tune the choice of the device to be implanted, taking into account that the reasons supporting the value of an extended device longevity as a clinical priority may differ according to the clinical setting (purely electrical diseases or left ventricular dysfunction/heart failure, respectively). From an economic point of view, extension of device longevity may have an important impact in reducing long-term costs of device therapy, with substantial daily savings in favour of devices with extended longevity, up to 30%, depending on clinical scenarios. In studies based on projections, an extension of device longevity allowed to calculate that the cost per day of ICDs may be substantially reduced, and this allows to overcome the frequent perception of ICD and CRT-D devices as treatments with unaffordable costs and to overturn the misconception that up-front costs are the only metric with which to value device treatments. In view of its clinical and economic value, device longevity should be a determining factor in device choice by physicians and healthcare commissioners and should be appropriately considered and valued in comparative tenders.